Exploring Culture in Locally Published English Textbooks for Primary Education in Turkey - Yasemin Kirkgöz; Reyhan Ağçam (Center for Educational Policy Studies Journal)
Since language and culture are closely interwoven, the integration of culture into textbooks used for teaching English as a second/foreign language has become a widely accepted phenomenon. This study investigates the cultural elements in locally published English textbooks used for Turkish primary schools following two major curriculum innovations in ELT. A total of 18 textbooks, of which 8 were published after the 1997 curriculum innovation and 10 after the curriculum innovation introduced in 2005, were investigated to find out the extent to which textbooks contain references to the source (Turkish) culture, the target (British/American) culture and the international target culture. A quantitative analysis of the cultural elements demonstrated that while references to the source and target cultures included in textbooks published between 1997 and 2005 outnumber international target cultural components, a different trend was obtained in the cultural analysis of books published after the 2005 curriculum innovation. The study reveals that representations of the source culture, the target culture and the international target culture are favoured in locally produced ELT textbooks in a fairly balanced way.